Drivers of firms’ debt ratios: evidence from Taiwanese and Turkish firms - Aren, Selim; Alpkan, Lutfihak; Sezen, Bulent; Guncu, Ziya Alper (Journal of Business Economics and Management, 2012)
This study investigates the drivers of debt ratios of the firms listed on the stock markets of two different countries, namely Turkey, a developing country and Taiwan, a newly developed country. The factors impacting short-term, long-term, and total debts are selected as EBIT (Earnings before Interest and Tax), ROE (Return on Equity), sales, total assets, fixed assets-total assets ratio, and depreciation-total assets ratio. The findings indicate that there are differences between Turkish and Taiwanese firms in terms of the drivers’ impacts on the debt structures of the firms. The proposed regression models work better on the data collected from Taiwan as compared to the data from Turkey. Possible reasons are discussed in the final section.Article in English.Įmonių skolos santykio nustatymas: Taivano ir Turkijos įmonių pavyzdžiuSantrauka. Šis tyrimas apima dviejų skirtingų, tačiau stipriai besivystančių šalių, t. y. Taivano ir Turkijos rinkose veikiančių kompanijų skolos santykio nustatymą. Pagrindiniais veiksniais, turinčiais įtakos trumpalaikėms, ilgalaikėms ir bendrosioms skoloms, buvo pasirinktas pelnas prieš sumokant palūkanas ir mokesčius (EBIT), nuosavo kapitalo grąža (ROE), pardavimo, bendrojo turto, ilgalaikio turto ir bendrojo turto santykis bei bendrojo turto nusidėvėjimo santykis. Autorių gauti rezultatai rodo, kad vis dėlto yra skirtumų tarp Turkijos ir Taivano įmonių bei tų įmonių skolų struktūros. Straipsnio autoriai taikė regresijos metodus, kurie Taivano situaciją atspindėjo geriau nei Turkijos, o kodėl taip nutiko, autoriai argumentuoja paskutiniame straipsnio skyriuje.Reikšminiai žodžiai: skola, santykis, kapitalo struktūra, vertinimo svertai, Turkija, Taivanas